ESSENCES FORESTIERES UTILISEES DANS LA FABRICATION DES ŒUVRES D’ART DANS LA VILLE DE KISANGANI, RD CONGO - Thierry, BENGWELA MONGOLU (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The study on forest trees used in the production of art works was conducted in Kisangani, in the Province of the Tshopo, in Democratic Republic of Congo. Technique of survey based on a questionnaire of open type and field personal observations have allowed this study. The results show after analysis that: The species used for the production of works of art in the city of kisangani are: Pericopsis elata; Priori balsamifera; Milletia laurentii; Diospyros spp.; Pterocarpus soyauxii. Caloncoba welwitchii The main art objects made in the city of Kisangani are: Masks; Statuettes; Whaling; Canoe; Mixers; Paddles; Mortars; Stepladders. Almost all of the species used in the craft of art works are those of first class, except for the Caloncoba welwitchii which is an essence of third class.